2008
DOI: 10.1038/mp.2008.65
|View full text |Cite
|
Sign up to set email alerts
|

A neural model of voluntary and automatic emotion regulation: implications for understanding the pathophysiology and neurodevelopment of bipolar disorder

Abstract: The ability to regulate emotions is an important part of adaptive functioning in society. Advances in cognitive and affective neuroscience and biological psychiatry have facilitated examination of neural systems that may be important for emotion regulation. In this critical review we first develop a neural model of emotion regulation that includes neural systems implicated in different voluntary and automatic emotion regulatory subprocesses. We then use this model as a theoretical framework to examine function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

94
1,116
3
25

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,175 publications
(1,238 citation statements)
references
References 209 publications
(253 reference statements)
94
1,116
3
25
Order By: Relevance
“…These results correspond well with findings from meta analyses investigating structural alterations in BD, repeatedly reporting altered insula and basal ganglia structure in BD compared with HC (Bora et al, 2012). Similarly, functional MRI studies highlighted the role of the insula for reward processing in BD (Phillips et al, 2008a).…”
Section: Reward Processing In Ud and Bdsupporting
confidence: 78%
“…These results correspond well with findings from meta analyses investigating structural alterations in BD, repeatedly reporting altered insula and basal ganglia structure in BD compared with HC (Bora et al, 2012). Similarly, functional MRI studies highlighted the role of the insula for reward processing in BD (Phillips et al, 2008a).…”
Section: Reward Processing In Ud and Bdsupporting
confidence: 78%
“…Depression has been conceptualized as a failure to recruit prefrontal top-down cognitive control to regulate emotion producing subcortical limbic activity (Phillips, Ladouceur, & Drevets, 2008). A meta-analysis of neuroimaging studies revealed evidence for the involvement of two neurocircuits in major depressive disorder.…”
Section: Treatment Mechanisms Of Neurostimulation In Trd a Neurobiolomentioning
confidence: 99%
“…BD is associated with dysfunction of emotion regulation (Phillips et al, 2008), which involves the initial steps of perception of information eliciting emotional arousal.…”
Section: Introductionmentioning
confidence: 99%